Dalmatian Silvanus: A Cognitive Approach to Reinterpretation of the Reliefs Representing Silvanus from Roman Dalmatia - Lulić, Josipa (2014)
The paper offers new interpretation of the sculptures from Roman Dalmatia representing Silvanus in the light of the cognitive theory.
ENG